Improve of Using Animation Videos in Speaking Skill on NarrativeText forSenior High School in Class X3 SMAN 17 Surabaya - Ari Cindy Agustina; Wijayadi; Nur Fitriah (PROCEEDING UMSURABAYA, 2026)
This study aims to analyze the effectiveness of using animation videostoenhance speaking skills in narrative text for Class X3 students at SMAN17 Surabaya. This research used a quantitative approach with a one-group experimental design. Data were collected through a pre-test using conventional teaching methods andapost-test after teaching with animation videos. The results showed that studentstaught with animation videos significantly improved their speaking skills, includingfluency, vocabulary, and storyline comprehension. Additionally, studentsdemonstrated higher motivation and engagement during lessons.